Modelling, simulation and warming impact assessment of a domestic-size absorption solar cooling system - Florides, Georgios A.; Kalogirou, Soteris A.; Tassou, Savvas A.; Wrobel, L. C. (My University, 2002)
In this paper the modelling, simulation and total equivalent warming impact (TEWI) of a domestic-size absorption solar cooling system is presented. The system consists of a solar collector, storage tank, a boiler and a LiBr–water absorption refrigerator. Experimentally determined heat and mass transfer coefficients were employed in the design and costing of an 11 kW cooling capacity solar driven absorption cooling machine which, from simulations, was found to have sufficient capacity to satisfy the cooling needs of a well insulated domestic dwelling. The system is modelled with the TRNSYS simulation program using appropriate equations predicting the performance of the unit. The final optimum system consists of 15 m2 compound parabolic collector tilted at 30° from horizontal and 600 l hot water storage tank. The total life cycle cost of a complete system, comprising the collector and the absorption unit, for a lifetime of 20 years will be of the order of C£ 13,380. The cost of the absorption system alone was determined to be C£ 4800. Economic analysis has shown that for such a system to be economically competitive compared to conventional cooling systems its capital cost should be below C£ 2000. The system however has a lower TEWI being 1.2 times smaller compared to conventional cooling systems.
Keywords: Absorption refrigeration; Solar cooling; Warming impact